Unveiling Teachers’ Perception: Cultural Influences on Educators' Decision-Making in High-Stakes Exams - Maya Puspitasari; Muhammad Arifin Pelawi (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
This study analyses the diverse motives of educators entering the teaching profession and their impact on pedagogical decisions during high-stakes exams. Semi-structured interviews with eight participants (six male and two female teachers) from secondary schools in Kabupaten Bandung, Jawa Barat, Indonesia, lasted up to forty minutes. These interviews aimed to elicit insights into the participants' beliefs on their professional calling.Three key themes emerged from the interviews' thematic analysis: the trajectory of a teacher's personal history, the influential role of degree choice, and the weight of accountability. Furthermore, the findings highlighted how gender identity not only influenced the teachers but also echoed across their familial spheres, guiding them towards a profession in education.This investigation underlined the critical significance of cultural beliefs in developing educators' motivations, which serve as the foundation of their professional identity. As a result, this identification has a substantial impact on their pedagogical practises in the classroom, particularly when confronted with the demands imposed by high-stakes exams. This study sheds insight into the intricacies underpinning educators' decision-making processes, particularly in circumstances typified by rigorous assessments, by providing a comprehensive view of the delicate interplay between cultural factors, individual motives, and professional practice.